Rapid on-farm multiplication of plantain and banana - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Two new methods of propagating plantain and banana have been developed by the National Horticultural Research Institute in Nigeria. Both plantains and bananas are a major food in West Africa, but availability of propagating material has limited the...